Exploring Students’ Perceptions of Circular Bioeconomy Practices through Plant Waste Utilization in Biology Education - Warda Murti; Sarnawiah Sarnawiah; Muh. Anas; Nana Erna (Biology Teaching and Learning, 2026)
Abstract Purpose: This study aimed to explore students’ perceptions of Circular Bioeconomy practices through plant waste utilization in biology education and to examine their implications for sustainability-oriented learning.Research Methodology: A descriptive quantitative approach was employed involving 160 Biology Education students from Patompo University, Maros Muslim University, and Muhammadiyah University of Makassar selected through purposive sampling. Data were collected using a Likert-scale questionnaire covering four indicators: conceptual understanding, plant waste utilization activities, instructional integration, and student engagement. Instrument validity was assessed through expert judgment and Pearson’s Product-Moment correlation, while reliability was measured using Cronbach’s alpha. Data were analyzed using descriptive statistics, including mean scores, percentages, and standard deviations.Results: The findings showed that students perceived Circular Bioeconomy practices in biology education at a moderate level. Although students demonstrated relatively good conceptual understanding of Circular Bioeconomy principles, practical activities involving plant waste utilization and experiential learning remained limited. The results revealed a gap between ecological awareness and the implementation of sustainability practices in biology learning.Conclusions: Sustainability-oriented biology education has not yet fully fostered students’ ecological literacy, sustainability competencies, and active environmental engagement. More contextual and experiential learning opportunities are needed to strengthen Circular Bioeconomy practices.Limitations: The study was limited to students from three universities in South Sulawesi and relied on self-reported questionnaire data.Contributions: This study contributes empirical evidence to the fields of biology education and sustainability education and provides insights for educators and curriculum developers in designing learning programs that integrate Circular Bioeconomy principles through plant waste utilization.Keywords: Circular Bioeconomy, Plant Waste Utilization, Biology Education.